Low molecular-weight phenolic compounds in natural and agglomerated cork stoppers - Pena-Neira, A; BartolomÉ, B; Cadahía, E; Hernández, T; Garcia-Vallejo, C; GONZALEZ-ADRADOS, J R; Suarez-Lepe, J A (SCIENCES DES ALIMENTS, 1999)
The low molecular-weight phenolic compounds in cork stoppers used for the closure of wine bottles are studied. Different phenolic acids (gallic, protocatechuic, vanillic, caffeic, ferulic and ellagic), aldehydes (protocatechuic, p-hydroxybenzoic, vanillin, ethylvanillin and coniferilic), and coumarins (aesculetin and scopoletin) were determined in natural cork stoppers (untreated and chlorine-bleached) and in agglomerated cork stoppers (unbleached and peroxide-bleached). The ketone 2,3-dihydroxy-1-guaiacylpropan-1-one and four ellagic-acid-type tannins were detected in natural stoppers. The amount of most of the phenolic compounds studied was higher in the natural cork stoppers than in agglomerated stoppers. In natural cork stoppers, an Increase in the content of caffeic and ferulic acids and vanillin was observed after chlorine bleaching. In agglomerated stoppers however, peroxide bleaching produced a decrease in the content of these same compounds.
Keywords: Cork; low molecular-weight phenolic; Stopper; stopper treatment